Necrotizing Fasciitis of the Nose Complicated with Cavernous Sinus Thrombosis - D. Swaminath; R. Narayanan; M. A. Orellana-Barrios; B. Temple (Case Reports in Infectious Diseases)
Necrotizing fasciitis is a rapidly progressive life threatening bacterial infection of the skin, the subcutaneous tissue, and the fascia. We present a case of necrotizing fasciitis involving the nose complicated by cavernous sinus thrombosis. Few cases of septic cavernous sinus thrombosis have been reported to be caused by cellulitis of the face but necrotizing fasciitis of the nose is rare. It is very important to recognize the early signs of cavernous thrombosis. Treatment for septic cavernous sinus thrombosis is controversial but early use of empirical antibiotics is imperative.